The Preliminary and Subsequent Stages to Integrating Pedagogical Innovation: The Crux of the Matter for the Innovator - Walder, Anne Mai (Alberta Journal of Educational Research, 2014)
Within the extremely competitive environment of higher education, professors make a conscious decision to engage in pedagogical innovation projects. Through this qualitative research, I revisit the experience of thirty-two innovators who gravitate between risks and uncertainty, particularly as they teach at a university where research prevails over teaching. The results provide us with in-depth insight into the specific conditions and processes of pedagogical innovation, shedding light on the optional stages and delineating those that appear to be fundamental to the innovation process. Dans le contexte extrêmement compétitif de l’enseignement supérieur, les professeurs choisissent consciemment d’entreprendre des projets d’ innovation pédagogique. Cette recherche qualitative porte sur les expériences de 32 innovateurs qui gravitent entre risques et incertitudes, notamment lorsqu’ils enseignent dans une université où la recherche prévaut sur l’enseignement. Les résultats permettent d’appréhender en profondeur les conditions et démarches spécifiques de l’innovation pédagogique en distinguant les étapes optionnelles de celles qui semblent fondamentales dans le processus l’innovation.